A poisonous cocktail: interplay of cereulide toxin and its structural isomers in emetic Bacillus cereus - Kranzler, Markus; Walser, Veronika; Stark, Timo D.; Ehling-Schulz, Monika (Frontiers in Cellular and Infection Microbiology, 2024)
Food intoxications evoked by emetic Bacillus cereus strains constitute a serious threat to public health, leading to emesis and severe organ failure. The emetic peptide toxin cereulide, assembled by the non-ribosomal peptide synthetase CesNRPS, cannot be eradicated from contaminated food by usual hygienic measures due to its molecular size and structural stability. Next to cereulide, diverse chemical variants have been described recently that are produced concurrently with cereulide by CesNRPS. However, the contribution of these isocereulides to the actual toxicity of emetic B. cereus, which produces a cocktail of these toxins in a certain ratio, is still elusive. Since cereulide isoforms have already been detected in food remnants from foodborne outbreaks, we aimed to gain insights into the composition of isocereulides and their impact on the overall toxicity of emetic B. cereus. The amounts and ratios of cereulide and isocereulides were determined in B. cereus grown under standard laboratory conditions and in a contaminated sample of fried rice balls responsible for one of the most severe food outbreaks caused by emetic B. cereus in recent years. The ratios of variants were determined as robust, produced either under laboratory or natural, food-poisoning conditions. Examination of their actual toxicity in human epithelial HEp2-cells revealed that isocereulides A-N, although accounting for only 10% of the total cereulide toxins, were responsible for about 40% of the total cytotoxicity. And his even though some of the isocereulides were less cytotoxic than cereulide when tested individually for cytotoxicity. To estimate the additive, synergistic or antagonistic effects of the single variants, each cereulide variant was mixed with cereulide in a 1:9 and 1:1 binary blend, respectively, and tested on human cells. The results showed additive and synergistic impacts of single variants, highlighting the importance of including not only cereulide but also the isocereulides in routine food and clinical diagnostics to achieve a realistic toxicity evaluation of emetic B. cereus in contaminated food as well as in patient samples linked to foodborne outbreaks. Since the individual isoforms confer different cell toxicity both alone and in association with cereulide, further investigations are needed to fully understand their cocktail effect.